Focusing on the Earth: Using Photography and Photo Elicitation as Instruments to Engage Children as Coresearchers in a Community Garden (LEARNing Landscapes, 2008)
In this article, the use of photographs and photo elicitation are used as models for engaging elementary children in collaborative research. Based on ethnographic research conducted in a community garden, the author illustrates how digital cameras act as a symbolic device that allow children to "pivot" (Vygotsky, 1978) into the world of researcher within the boundaries of a natured setting. Using photo-narratives constructed by three children which document their outside, social experiences in the garden, the author suggests that their still images and accompanying narratives expose complex interrelationships between empathy, exploration and the natural environment.
Keywords: arts; education; photographs; elementary students; engagement; collaborative research; ethnography; photo-narrative; empathy; natural environment